Single droplet detection of immune checkpoints on a multiplexed electrohydrodynamic biosensor. Issue 23 (28th October 2019) - Wuethrich, Alain; Rajkumar, Aswin Raj; Shanmugasundaram, Karthik Balaji; Reza, Kamil K.; Dey, Shuvashis; Howard, Christopher B.; Sina, Abu Ali Ibn; Trau, Matt
Abstract : A nanofluidic mixing-enhanced biosensor enables parallel detection of soluble PD-1, PD-L1, and LAG-3 immune checkpoints in minute liquid biopsy samples. Abstract : Monitoring soluble immune checkpoints in circulating fluids has the potential for minimally-invasive diagnostics and personalised therapy in precision medicine. Yet, the sensitive detection of multiple immune checkpoints from small volumes of liquid biopsy samples is challenging. In this study, we develop a multiplexed immune checkpoint biosensor (MICB) for parallel detection of soluble immune checkpoints PD-1, PD-L1, and LAG-3. MICB integrates a microfluidic sandwich immunoassay using engineered single chain variable fragments and alternating current electrohydrodynamic in situ nanofluidic mixing for promoting biosensor–target interaction and reducing non-specific non-target binding. MICB provides advantages of simultaneous analysis of up to 28 samples in <2 h, requires as little as a single sample drop ( i.e., 20 μL) per target immune checkpoint, and applies high-affinity yeast cell-derived single chain variable fragments as a cost-effective alternative to monoclonal antibodies. We investigate the assay performance of MICB and demonstrate its capability for accurate immune checkpoint detection in simulated patient serum samples at clinically-relevant levels. MICB provides a dynamic range of 5 to 200 pg mL −1 for PD-1 and PD-L1, and 50 to 1000 pg mL −1 for LAG-3 with a coefficient of variation <13.8%. Sensitive immune checkpoint detection was achieved with limits of detection values of 5 pg mL −1 for PD-1, 5 pg mL −1 for PD-L1, and 50 pg mL −1 for LAG-3. The multiplexing capability, sensitivity, and relative assay simplicity of MICB make it capable of serving as a bioanalytical tool for immune checkpoint therapy monitoring.